Hubungan Lingkungan dan Motivasi Kerja dengan Stres Kerja Perawat di Ruangan Mawar RSUD Pasangkayu - Benny H.L Situmorang; Mar’aeni Mar’aeni (Neolectura, 2020)
The observation and interview reported toward nurses in Mawar Ward of Pasangkayu General Hospital shown that have work overload for nurses such as patient administration assignment, nutrient providing care, pharmacy assignment that could make work stress for them. The aims of research to analys the correlation of enviorenment and work motivation toward work stress of nurses in Mawar Ward Pasangkayu General Hospital. This is quantitative research with cross sectional design. Total of population is 33 staffs nurses who work in Mawar Ward of Pasangkayu General Hospital and sampling also 33 respondents. Data analysed by Chi-Square test with work enviorenment and work motivation as a independent variable and nurses work stress as a dependent variable. The research result shown that have correlation between work enviorenment and nurses work stress in Mawar Ward Pasangkayu General Hospital with p value 0,002, and have correlation between work motivation and work stress of nurses in Mawar Ward Pasangkayu General Hospital with p value 0,020. Conclusion of research mentioned that have correlation of work enviorenment and work motivation toward work stress of nurses in Mawar Ward Pasangkayu General Hospital.